2015
DOI: 10.3390/en81212433
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Train Operation in Multiple Interstations with Multi-Population Genetic Algorithm

Abstract: Subway systems consume a large amount of energy each year. How to reduce the energy consumption of subway systems has already become an issue of concern in recent years. This paper proposes an energy-efficient approach to reduce the traction energy by optimizing the train operation for multiple interstations. Both the trip time and driving strategy are considered in the proposed optimization approach. Firstly, a bi-level programming model of multiple interstations is developed for the energy-efficient train op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 29 publications
0
28
0
2
Order By: Relevance
“…It is proved to be efficient in solving NP-hard optimization problems in the transportation field [25][26][27][28]. This method was also used by Lee et al [13] to find a solution to the A/B mode-based skipstop operation problem.…”
Section: Solution Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…It is proved to be efficient in solving NP-hard optimization problems in the transportation field [25][26][27][28]. This method was also used by Lee et al [13] to find a solution to the A/B mode-based skipstop operation problem.…”
Section: Solution Approachmentioning
confidence: 99%
“…As our study targets off-peak operation, was set to be 15 minutes. The time loss was calculated based on the reachable maximum speed max using formulation (26). Here is the maximum acceleration rate and is the maximum deceleration rate.…”
Section: Data Processing and Experiments Setupmentioning
confidence: 99%
“…A large amount of previous studies [5,15,18,21,[53][54][55] have demonstrated that the energy-efficient driving strategies of each section will be maximum traction (MT), coasting (CO) and maximum braking (MB). Additionally, in each phase, train movement is as in Equation (18).…”
Section: Energy Consumption Calculationmentioning
confidence: 99%
“…Li and Lo [34] proposed an integrated energy-efficient operation model to jointly optimize the timetable and speed profile with minimum net energy consumption. Huang et al [21] proposes an energy-efficient approach to reduce the traction energy by optimizing the train operation for multiple sections, considering both the trip time and driving strategy. Although a set of work has been done with a comprehensive view, more realistic work is needed to apply the optimal approach into practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation